2004
DOI: 10.1038/sj.eye.6700669
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Orbscan and Ultrasound pachymetry in the measurement of central corneal thickness

Abstract: Measurement of central corneal thickness (CCT) is of ever increasing importance to glaucoma specialists. Studies indicate that measurements of intraocular pressure (IOP), especially when taken by applanation tonometry, are influenced by corneal thickness. A recent meta-analysis showed that a 10% difference in CCT would result in an average of 3.470.9 mmHg difference in IOP (1.1 mmHg for normal eyes, 2.5 mmHg for chronically diseased eyes, and 10.0 mmHg in eyes with acute onset active disease).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…49 Most investigations of epithelial thickness report on the central cornea only. While a few studies have documented the peripheral thickness along the horizontal meridian, 10–13 very few have studied the thickness along the peripheral vertical meridian.…”
Section: Introductionmentioning
confidence: 99%
“…49 Most investigations of epithelial thickness report on the central cornea only. While a few studies have documented the peripheral thickness along the horizontal meridian, 10–13 very few have studied the thickness along the peripheral vertical meridian.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been made comparing Orbscan with ultrasound pachymetry for measurement of corneal thickness, some of which are summarized in Table 1 4, ,9,10,11,12,13,14,15,16,17,18,19. From the Table, considerable variability is seen in comparison of mean CCT for groups of normal eyes when comparing ultrasound pachymetry with Orbscan measurements (using the manufacturer’s recommended acoustic correction factor of 0.92), with differences ranging from −21 to 33 µm.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been reported that the order of measurement by different ultrasonic pachymeters has no effect on thickness. 26 The Orbscan II measurements, in eyes without previous corneal surgery (group 1), were found to be comparable with those of the three tested ultrasound instruments, differing from the findings of Radford et al 9 Fakhry et al 25 found no difference, even in post-LASIK eyes. One possible reason for a difference in these and other reports is the acoustic level setting.…”
Section: Discussionmentioning
confidence: 73%
“…A review of methods for measuring CCT with a range of thickness and the impact of CCT on measuring intraocular pressure was recently reported by Doughty and Zaman 7 using a meta-analysis. The most common method to determine CCT is ultrasonic pachymetry, which has been claimed by some authors 8,9 to be the gold standard.…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation